Effect of Sapodilla (ManilkarazapotaL.) Leaves Extract on Pancreasof AlloxanInduced Mice: A Histopathological Study - Mela Septiani; Tridiganita Intan Solikhah; Boedi Setiawan (The Indian Veterinary Journal, 2025)
Diabetes mellitusis a metabolic disorder in the form of high levels of glucose in the blood. This study was conducted to determine the effect of Manilkara zapota leaf extract (MZLE) on alloxan-induced mice. 25 male mice ± 3 months, 25-35 g, treated with P1 (MZLE 140 mg/kg), P2 (MZLE 70mg/kg), K+ (Pioglitazone 20 mg/kg), P0 (normal control) and K- (diabetescontrol). Pancreas was taken on day 14 after being given therapy. Data analysis by Kruskal Wallis and MannWhitney. MZLE 140 mg/kg showed that the highest pancreatic protection compared to MZLE 70 mg/kg and pioglitazone 20 mg/kg.